O lord… where is my fetus? : a case report of pseudocyesis - Yanti, Linda (Universitas Muhammadiyah Purwokerto, 2019)
Introduction: Pseudocyesis is a condition in which a woman presents various signs and symptoms of pregnancy such as menstruation, nausea, vomiting, enlargement of the womb, weight gain, and other pregnancy symptoms. Furthermore, urine test may notice false positive result.Case presentation: It was illustrated with unusual case of pseudocyesis to a 44 year old woman reported fetal loss at the age of six months of pregnancy to a health worker in Lampung province.Conclusion: Pseudocyesis symptoms are just common pregnancy, but actually it is a false pregnancy.